The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.adolescence.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Youth experiences with multiple types of prejudice‐based harassment

Abstract: Despite prejudice‐based harassment's associations with serious physical and mental health risks, research examining multiple forms of harassment among children/adolescents is lacking. This study documents the prevalence of prejudice‐based harassment (i.e., harassment on the basis of gender, race/ethnicity, weight or physical appearance, sexual orientation, and disability status) among a large, statewide, school‐based Midwestern U.S. sample of 162,034 adolescents. Weight‐/appearance‐based harassment was most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
112
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 40 publications
7
112
1
1
Order By: Relevance
“…The results of this study also show that peer victimisation is based on social prejudices. Research on discriminatory bullying is still in the early stages (Bucchianeri et al, 2016, Elamé, 2013Hunter et al, 2010;Russell et al, 2012). …”
Section: Limitations and Implications For Practice And Future Researchmentioning
confidence: 99%
“…The results of this study also show that peer victimisation is based on social prejudices. Research on discriminatory bullying is still in the early stages (Bucchianeri et al, 2016, Elamé, 2013Hunter et al, 2010;Russell et al, 2012). …”
Section: Limitations and Implications For Practice And Future Researchmentioning
confidence: 99%
“…In fact, studies note effects of bias-based bullying that are as large or larger than the effects seen for general bullying victimization [44,49,50]. LGBTQ youth are more likely than their straight cisgender peers to be the targets of bias-based bullying [7,32,42,51,52], and importantly, this is not just bias related to their sexual orientation and gender identity. For example, LGBQ youth are more likely than their straight peers to be the targets of bullying based on race, weight/appearance and ability, even after controlling for race/ethnicity, weight and ability status [42].…”
Section: Introductionmentioning
confidence: 99%
“…Variation within these groups, however, must also be considered. For example several studies have noted differences in general bullying and bias-based bullying rates between lesbian, gay, bisexual, questioning, and straight youth who report same sex sexual activity [14,42], all of whom are typically grouped together as LGBQ. Research evidence is building that youth who identify as bisexual report elevated rates of health-risk and health-compromising experiences, and bullying is among them [10,35,71].…”
Section: Introductionmentioning
confidence: 99%
“…However, bullying prevention efforts often focus on general, rather than bias-based, bullying (Earnshaw et al 2018;Shetgiri et al 2015), and those efforts that do target bias-based bullying tend to focus on a single type (e.g., heterosexist victimization alone), rather than targeting overlapping bias-based bullying (Earnshaw et al 2018). Yet, the reality is that LGBQ youth may simultaneously experience other types, including racist, cis-sexist, and able-ist bullying (Bucchianeri et al 2016;Gower et al 2018b;Kahn and Lindstrom 2015). Informed by the intersectionality theory, which highlights the interconnection and co-construction of multiple oppressive systems (Crenshaw 1991), this study describes how multiple forms of bias-based bullying victimization overlap among LGBQ youth.…”
mentioning
confidence: 98%
“…Marginalized youth (e.g., LGBQ youth, youth of color, youth with disabilities, transgender, and gender diverse youth) may report higher rates of bias-based bullying than their peers with majority identities (e.g., straight, White, and cisgender). Youth of color, LGBTQ youth, youth with disabilities, and those who are overweight or obese report disproportionate rates of general and bias-based bullying compared with their peers (Bucchianeri et al 2016;Kosciw et al 2018;Shetgiri et al 2015). For example, a recent survey of school climate found that nearly three-quarters of LGBTQ youth reported experiencing bias-based bullying due to their sexual orientation and nearly half due to gender identity (Kosciw et al 2018).…”
mentioning
confidence: 99%